Too Much Investment: A Problem of Asymmetric Information - Meza, David De; Webb, David C. (Quarterly Journal of Economics, 1987)
This paper shows that under plausible assumptions, the inability of lenders to discover all of the relevant characteristics of borrowers results in investment in excess of the socially efficient level. Raising the rate of interest above the free market level will restore optimality. This conflicts with generally held views and is contrasted with the Stiglitz-Weiss model. It is shown that the assumptions which yield overinvestment support debt as the equilibrium method of finance. However, under the Stiglitz-Weiss assumptions, used to derive an underinvestment result, equity is shown to be the equilibrium method of finance.